1995
DOI: 10.1021/bi00037a023
|View full text |Cite
|
Sign up to set email alerts
|

Surface lysine residues modulate the collisional transfer of fatty acid from adipocyte fatty acid binding protein to membranes

Abstract: The transfer of unesterified fatty acids (FA) from adipocyte fatty acid binding protein (A-FABP) to phospholipid membranes is proposed to occur via a collisional mechanism involving transient ionic and hydrophobic interactions [Wootan & Storch (1994) J. Biol. Chem. 269, 10517-10523]. In particular, it was suggested that membrane acidic phospholipids might specifically interact with basic residues on the surface of A-FABP. Here we addressed whether lysine residues on the surface of the protein are involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
1
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 34 publications
3
67
1
2
Order By: Relevance
“…These results suggest that in general, stability of the apo-or holoprotein is not coupled to ligand affinity. Consistent with this interpretation, Herr et al (8) have recently demonstrated with chemically modified ALBP that when all surface lysine residues are acetylated, the stability of the protein is affected (destabilized) while the affinity is unaltered. Similarly, in studies of cellular retinoic acid-binding protein 1 (25), substitution mutations of critical arginine residues rendered the protein unable to bind retinoic acid but stabilized the molecule to thermal denaturation.…”
Section: Discussionmentioning
confidence: 72%
“…These results suggest that in general, stability of the apo-or holoprotein is not coupled to ligand affinity. Consistent with this interpretation, Herr et al (8) have recently demonstrated with chemically modified ALBP that when all surface lysine residues are acetylated, the stability of the protein is affected (destabilized) while the affinity is unaltered. Similarly, in studies of cellular retinoic acid-binding protein 1 (25), substitution mutations of critical arginine residues rendered the protein unable to bind retinoic acid but stabilized the molecule to thermal denaturation.…”
Section: Discussionmentioning
confidence: 72%
“…Many forms of FABP (e.g., from heart, adipocyte, and intestine) transfer fatty acids to and from membranes during brief collisional encounters (7,10,12,13,31). This process involves an interaction between a positively charged region of the binding protein and negative charges on the membrane surface, resulting in a conformational change that permits direct transfer of fatty acid between the protein binding site and the membrane (5,7,10,11,30). We will refer to this FABP class as being membrane active.…”
mentioning
confidence: 99%
“…A FABP has been proposed to be involved in the intracellular trafficking and targeting of fatty acids (3,4). In vitro studies have indicated that the transfer of fatty acids from AFABP to vesicles occurs during direct collisional interactions between the protein and acceptor membranes; however, the fatty acid transfer properties of KFABP have not been reported.…”
mentioning
confidence: 99%
“…R e c o mbinant murine AFABP and KFABP were expressed in Escherichia coli h o s t strain BL21 (DE3) and purified using gel filtration, ion exchange, and delipidation chromatography, as previously described (4,15). The rate of transfer of 12-(9-anthroyloxy)oleate (12AO) from AFABP and KFABP to small unilamellar vesicles (SUVs) was determined using a previously detailed resonance energy transfer assay (4,15). Transfer was monitored at 25°C in 40 mmol/l Tr i s -1 0 0 mmol/l NaCl, pH 7.4.…”
mentioning
confidence: 99%